Enhancing seedling performance direct seeded rice under anaerobic germination condition by seed invigoration - Wahyuni, Sri; Agustiani, Nurwulan; Rumanti, Indrastuti Apri; Margaret, Swisci; Salma, Selly; Ardhiyanti, Shinta Dewi (Penerbit Universiti Kebangsaan Malaysia, 2024)
In an effort to address labor scarcity and enhance the cropping index in tidal swamp areas, farmers utilize direct seeding techniques. However, flooded conditions due to tides and ebb can hinder seed germination. This study aimed to obtain the best invigoration treatment for improving seedling establishment and growth in South Sumatra’s tidal swamp hotspots. In the first part of the study, 19 different seed treatments were tested on the swamp rice variety, Inpara 9, in a greenhouse. These treatments included hardening, priming, thermal treatment, and controls. Soluble sugar content and α-amylase activities of treated seeds were analyzed in the lab. The results showed that the invigorated seeds outperformed the control group in terms of seedling growth and development when they were planted directly in the ground under both anaerobic germination (AG) and anaerobic germination with extra FeSO4 added to the soil (AG+Fe) conditions. All treated seeds also exhibited higher soluble sugar and α-amylase activities. A follow-up experiment in a hotspot area assessed the effectiveness of the top nine seed treatments from the first experiment under AG conditions. The flooded level was managed at around 10 cm during the experiment and Inpara-9 was the variety planted. All invigorated seeds exhibited superior seedling establishment and growth compared to the control on in-situ swampy land. Hardening using Trichoderma yielded the highest seedling establishment and performance, indicated by greater root and shoot dry weight than other treatments, followed by hardening with Methylobacterium td-J7 and Methylobacterium td-tpb3.